The Cost Effectiveness of Mental Health Treatment in the Lifetime of Older Adults with HIV in New York City: A Markov Approach - DelaCruz, Juan J. (Pharmacoecon Open, 2020)
BACKGROUND: There are noticeable gaps in knowledge regarding the cost and effectiveness of integrated medical and behavioral services for older adults with HIV. Their lifespan is close to the population’s level but their quality of life has sharply declined due to depression and substance use. Mental health disorders are widespread among an aging population with HIV. OBJECTIVE: The aim of this study was to build a decision analytic model to evaluate medical interventions with and without mental health treatment using primary data of 139 older adults with HIV and health outcomes from the literature. METHODS: We tracked the progression of depression and cumulative deaths among older adults with HIV using a Markov model with 50 annual cycles through three health states. Deterministic and probabilistic sensitivity analyses addressed uncertainty in estimating the parameters and around the model’s assumptions. RESULTS: An integrated medical and behavioral care system is cost effective at a willingness to pay of $50,000 per QALY compared with medical care only. The incremental cost was $516,452 and the incremental effectiveness was 38.8 quality-adjusted life-years (QALY), with an incremental cost-effectiveness ratio of $13,316 per QALY. CONCLUSIONS: Appropriate and efficacious referrals to integrated medical + behavioral services, either in the same facility or connected to their primary care doctor, are instrumental to reverse loses in quality of life and avoid premature death. If mental health is left unattended, HIV would progress, causing declines in quality of life and ultimately triggering premature death. Reliable data on the cost and effectiveness of different types of HIV integrated services are needed.